EVALUATION OF DESIGN QUALITY OF ONLINE BIOCHEMISTRY ANIMATIONS USING MAYER’S PRINCIPLES - Ravi Kishore Polepalli (National Journal of Medical Research, 2017)
Introduction: Online animations are accessed by MBBS Ist year students in order to learn complex concepts in Biochemistry. Multimedia learning principles proposed by Richard E Mayer, have been used in the design of animations to enhance learning. There is a paucity studies that have evaluated the design of animations in Biochemistry based on multimedia learning principles. In this study, our aim was to evaluate the design quality of online animations in Biochemistry using a framework based on Mayer’s multimedia learning Principles.